1997
DOI: 10.1038/bjc.1997.310
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein secretion is inhibited by oestradiol and stimulated by antioestrogens in KPL-3C human breast cancer cells

Abstract: Summary We recently established a human breast cancer cell line, KPL-3C, from a breast cancer patient with humoral hypercalcaemia. This cell line possesses oestrogen receptor (ER) and secretes parathyroid hormone-related protein (PTHrP) into medium. To investigate the effects of oestrogen and antioestrogens on PTHrP secretion, KPL-3C cells were cultured for 48 h in an oestrogen-eliminated medium with 17,B-oestradiol (E2), tamoxifen (TAM) and/or a pure antioestrogen, IC1182,780 (ICI), and PTHrP secretion was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…If PTHrP does act in a negative feedback loop to restrain the proliferative effects of estrogen, one might expect that expression of PTHrP or its receptor would be modified by estrogen. Although estrogen has been reported to upregulate, downregulate or not change the concentrations of PTHrP in breast cancer cell lines (Kurebayashi & Sonoo 1997, Funk & Wei 1998, Sugimoto et al 1999, we have found no evidence that hormone treatment affects levels of whole gland PTHrP or PTH-1R mRNA in early adolescent mice (unpublished results). However, it has been reported that the production of PTHrP by normal mammary epithelial cells in culture is enhanced by treatment with either EGF or TGF- (Ferrari et al 1992, 1994, Sebag et al 1994, Yin et al 1999.…”
Section: Discussionmentioning
confidence: 52%
“…If PTHrP does act in a negative feedback loop to restrain the proliferative effects of estrogen, one might expect that expression of PTHrP or its receptor would be modified by estrogen. Although estrogen has been reported to upregulate, downregulate or not change the concentrations of PTHrP in breast cancer cell lines (Kurebayashi & Sonoo 1997, Funk & Wei 1998, Sugimoto et al 1999, we have found no evidence that hormone treatment affects levels of whole gland PTHrP or PTH-1R mRNA in early adolescent mice (unpublished results). However, it has been reported that the production of PTHrP by normal mammary epithelial cells in culture is enhanced by treatment with either EGF or TGF- (Ferrari et al 1992, 1994, Sebag et al 1994, Yin et al 1999.…”
Section: Discussionmentioning
confidence: 52%
“…18 In contrast, when ROS 17/2.8 cells were treated with DEX for 6 and 24 h, the specific binding of 125 I-PTHrP-1-36 was increased, but when the same cells were treated with progesterone the effect of DEX on PTH/PTHrP-R expression was diminished. 19 There are some comparable data from KPL-3C and MCF7 cell lines on the effect of phorbol ester, steroid hormones, anti-estrogens and extracellular matrix (ECM) [26][27][28][29] but no reports on the effects of EGF, 1,25DHCC and DEX on PTH/PTHrP-R protein or gene expression in breast cancer cells. Nevertheless the data here suggest an additional mechanism by which the use of vitamin D analogues may act to suppress the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…We have already demonstrated the in vitro anti‐proliferative and pro‐invasive effect exerted on the carcinoma cell line 8701‐BC and some derived clones by PTHrP [11,12], which has been therefore regarded also as one of the key elements potentially involved in mammary tumorigenesis in vivo. Nonetheless, the regulation of PTHrP and PTHrP‐R expression and iPTHrP secretion by breast cancer cells has been poorly investigated, the unique data being those regarding the effect of phorbol ester, steroid hormones and anti‐estrogens on KPL‐3C and MCF7 cell lines [33–35].…”
Section: Discussionmentioning
confidence: 99%